The Implementation of Multicultural Islamic Religious Education Model at Darul Muhajirin Praya High School - Hamdan, Hamdan; Nashuddin, Nashuddin; Fadli, Adi (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to find a model and implementation of multicultural Islamic religious education at Darul Muhajirin Praya High School. Design/methods/approach – This research is qualitative research. The data were obtained through observation, interview, and documentation. The data analysis techniques used are the process of data collection, data reduction, data presentation, and conclusions. Findings – The model and implementation of multicultural Islamic religious education at Darul Muhajirin Praya High School are illustrated by the existence of a curriculum design that is integrated with the school's vision and a multicultural perspective. The implementation model of multicultural Islamic religious education included the application of Problem Based Learning (PBL) methods, Student Leadership Basic Training (SLBT) programs, and school cultures such as congregational prayers, Friday prayers at the Great Mosque of Praya, religious discussions across schools, and individual and social piety. Research implications/limitations – This study provides an overview of the model and implementation of multicultural Islamic religious education through the study of case studies in high schools. This study presents findings that can have implications for the direction of determining Islamic education and learning policies in schools. However, this study is limited to the case studies studied so that it allows for different conditions in different cases. Originality/value – This study found the model and implementation of multicultural Islamic religious education at Darul Muhajirin Praya High School. This study presents findings to fill the gaps that occur in the Islamic religious education process, and this research provides an explanation related to school efforts in managing the reality of multicultural life.